Multidimensional in Integrated Islamic Schools Based on Web Technology: Integration of Al-Qur’an Learning Modules and Daily Activities - Solihin, Muhammad Yusuf Baihaqi Solihin; Dwi Ratnasari; Sri Endang Anjarwani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2025)
Currently, the manual system of report card assessors is no longer considered adequate for handling the workload. The process of assessing student grades on SDIT Anak Sholeh Mataram report cards which still uses conventional methods causes the assessment service process to be less than optimal. Therefore, to overcome these difficulties, a web-based e-report information system was designed using the PHP programming language and using the MySQL database to process report card filling data. This web-based e-report is not only used to fill in academic grades but there are other assessments that can be used, namely assessments in the context of tahfiz and tahsin and assessing students' daily activities. The method used in web development this web-based e-report information system is the rapid application development (RAD) method with several stages of needs analysis, system design, coding and testing, program implementation, and maintenance. This method is used because it can shorten the time in developing an information system than traditional methods. Based on the questionnaire with 10 questions given, there were 78% who agreed with the creation of the application.